2022
DOI: 10.1155/2022/4235305
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses of Stromal-Immune Score-Related Competing Endogenous RNA Networks In Colon Adenocarcinoma

Abstract: Although recent clinical investigations emphasize the roles of myriad diversities of RNAs in stromal and immune components in the tumor microenvironment, especially in colon adenocarcinoma, however, analyses of “competing endogenous RNAs (ceRNA)” network in association with stromal and immune scores have yet to be determined. This study was conducted to explore the regulatory mechanisms of a stromal-immune score-based ceRNA network in colon adenocarcinoma. Stromal and immune scores of colon adenocarcinoma tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the TME related signatures analysis revealed that CD8 T cell effector and immune checkpoint associated pathway genes were higher in the low‐risk group than in the high‐risk group (Figure 5C). Previous studies revealed that colon adenocarcinoma patients with a higher immune score and more infiltration of antitumor immune cells have a better survival outcome 17–19 . Therefore, we speculated that the better prognosis of the low‐risk group might be related to the more favorable antitumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the TME related signatures analysis revealed that CD8 T cell effector and immune checkpoint associated pathway genes were higher in the low‐risk group than in the high‐risk group (Figure 5C). Previous studies revealed that colon adenocarcinoma patients with a higher immune score and more infiltration of antitumor immune cells have a better survival outcome 17–19 . Therefore, we speculated that the better prognosis of the low‐risk group might be related to the more favorable antitumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies revealed that colon adenocarcinoma patients with a higher immune score and more infiltration of antitumor immune cells have a better survival outcome. 17 , 18 , 19 Therefore, we speculated that the better prognosis of the low‐risk group might be related to the more favorable antitumor immune microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…In our current work, we found that there was a clear link between the hypoxia score and the amount of COPZ1 in several cancers. Previous studies revealed that a higher immune score was correlated with better survival outcomes [ 45 , 46 ]. We further discovered that the infiltration of antitumor immune cells was higher in the patients with low COPZ1 expression, such as B cells, Neutrophil, CD8+T cells, CD4+T cells and M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complex TME in GBM, the connections between 22 immune cells activity and the prognostic signature were investigated using the Cell-type Identification By Estimating Relative Subsets Of RNA Transcripts (CIBERSORT) analysis ( 28 ). Moreover, the immune score, Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE) score, and stromal score were calculated by the ESTIMATE algorithm ( 29 ).…”
Section: Methodsmentioning
confidence: 99%